Literature and National Consciousness of the Greek Minority in NorthernEpirus - Frantzi, Anteia (The Historical Review/La Revue Historique, 2007)
The first period of Albanian rule in Northern Epirus, from 1912 to 1945, witnessed a continuation of the oral tradition enriched by the experience of the unceasing struggle for liberation. It should be stressed that what we now call "literature of the ethnic Greek minority of Albania" is in fact nothing but an integral part of Greek literature. It is the literary output of the Greek inhabitants of the area who, despite the adverse political developments that left them outside the borders of the Greek state, maintained their creativity and their Greek identity. From 1945 onwards, with the establishment of the People's Republic of Albania, any attempt to assess the literature of the Greek minority in Northern Epirus stumbles upon the political and national dichotomy of the land and its people. Firstly, the writers who identified themselves with the Communist ideals were following the principles of Socialist Realism. Secondly, those who followed a path of silent resistance and struggled for the preservation of the Greek language reverted to allegory and cryptic writing.